English and American tool builders - Roe, Joseph Wickham, 1871-1960 (Salt Lake City, UT : Project Gutenberg, 2023)
"English and American Tool Builders" by Joseph Wickham Roe is a historical account written in the early 20th century. This work delves into the significant contributions of various tool builders in England and America, highlighting figures like Henry Maudslay and Eli Whitney, whose innovations laid the groundwork for modern industrial manufacturing. Roe emphasizes the critical, yet often overlooked, role of these pioneers in the evolution of machine tools, which are foundational to all subsequent industrial arts. At the start of the book, the author explains the book's purpose: to illuminate the essential work of tool builders and their influence on modern industry, contrasting their legacy with that of more recognized figures like statesmen and soldiers. He positions the tool builders not just as skilled artisans but as creative minds who significantly advanced mechanical technology. The opening sections explore the state of machine tools in the late 18th century and the advancements that arose during this transformative period, laying the groundwork for the detailed biographies of key figures that follow in subsequent chapters. (This is an automatically generated summary.)
Release date is 2023-11-05
deaurider, Harry Lamé and the Online Distributed Proofreading Team at https://www.pgdp.net (This file was produced from images generously made available by The Internet Archive)
Keywords: Industrial arts -- Biography; Machine-tools